Risk of New-Diagnosed Atrial Fibrillation After Transient Ischemic Attack - Purroy, Francisco; Vicente-Pascual, Mikel; Arque, Gloria; Begue, Robert; Farre, Joan; Gallego, Yhovany; Gil-Villar, Maria Pilar; Mauri, Gerard; Montalà, Nuria; Pereira, Cristina; Torres-Querol, Coral; Vazquez-Justes, Daniel (Frontiers in Neurology, 2022)
Background: Transient ischemic attack (TIA) provides a unique opportunity to optimize secondary preventive treatments to avoid subsequent ischemic stroke (SIS). Although atrial fibrillation (AF) is the leading cause of cardioembolism in IS and anticoagulation prevents stroke recurrence (SR), limited data exists about the risk of new-diagnosed AF (NDAF) after TIA and the consequences of the diagnostic delay. The aim of our study was to determine this risk in a cohort of TIA patients with long-term follow-up. Methods: We carried out a prospective cohort study of 723 consecutive TIA patients from January 2006 to June 2010. Median follow-up was 6.5 (5.0-9.6) years. In a subgroup of 204 (28.2%) consecutive patients, a panel of biomarkers was assessed during the first 24 h of the onset of symptoms. Multivariate analyses were performed to find out the associated factors of NDAF. Kaplan-Meier analysis was also performed to analyzed risk of SIS. Results: NDAF was indentified in 116 (16.0%) patients: 42 (36.2%) during admission, 18 (15.5%) within first year, 29 (25%) between one and five years and 27 (23.3%) beyond 5 years. NDAF was associated with sex (female) (hazard ratio [HR] 1.61 [95% CI, 1.07- 2.41]), age (HR 1.05 [95% CI, 1.03-1.07]), previous ischemic heart disease (IHD) (HR 1.84, [95% CI 1.15-2.97]) and cortical DWI pattern (HR 2.81 [95% CI , 1.87-4.21]). In the Kaplan-Meier analysis, NT-proBNP ≥218.2 pg/ml (log-rank test P<0.001) was associated with significant risk of NDAF during the first five years of follow-up. Patients with NDAF after admission and before five years of follow-up had the highest risk of SIS (P=0.002). Conclusion: The risk of NDAF after TIA is clinically relevant. We identified clinical and neuroimaging factors of NDAF. In addition, NT-proBNP was related to NDAF. Our results can be used to evaluate the benefit of long-term cardiac monitoring in selected patients.